Comparison of different methods of nasogastric tube insertion in anesthetized and intubated patients - Kavakli,Ali Sait (2017)
Abstract Background Nasogastric tube insertion may be difficult in anesthetized and intubated patients with head in the neutral position. Several techniques are available for the successful insertion of nasogastric tube. The primary aim of this study was to investigate the difference in the first attempt success rate of different techniques for insertion of nasogastric tube. Secondary aim was to investigate the difference of the duration of insertion using the selected technique, complications during insertion such as kinking and mucosal bleeding. Material and methods 200 adult patients, who received general anesthesia for elective abdominal surgeries that required nasogastric tube insertion, were randomized into four groups: Conventional group (Group C), head in the lateral position group (Group L), endotracheal tube assisted group (Group ET) and McGrath video laryngoscope group (Group MG). Success rates, duration of insertion and complications were noted. Results Success rates of nasogastric tube insertion in first attempt and overall were lower in Group C than Group ET and Group MG. Mean duration and total time for successful insertion of NG tube in first attempt were significantly longer in Group ET. Kinking was higher in Group C. Mucosal bleeding was statistically lower in Group MG. Conclusion Use of video laryngoscope and endotracheal tube assistance during NG tube insertion compared with conventional technique increase the success rate and reduce the kinking in anesthetized and intubated adult patients. Use of video laryngoscope during nasogastric tube insertion compared to other techniques reduces the mucosal bleeding in anesthetized and intubated adult patients.